Biodegradable binary blend of poly(lactic acid) / polypropylene via twin-screw extruder : preparation and characterization - Rudzaimi, M; Mat Piah, Mohd Bijarimi; Hafidzah, Farah; Alhadadi, Waleed; Desa, Mohd Saiful Zaidi; Ahmad, Mohammad Norazmi (American Institute of Physics, 2021)
In this work, a biodegradable poly(lactic acid) (PLA) and polypropylene (PP) were melt blended at various compositions in a twin-screw extruder. The binary blend systems of PLA/PP were then characterised for thermal, mechanical, and morphological properties. Thermal analysis by DSC showed that the melting temperature, Tm, increased about 5o C when the composition of PLA was reduced from 60% to 40% wt. The tensile strain showed an improvement of 29.24% due to the ability of PP part to enhance the flexibility of PLA. The FTIR results revealed that PLA/PP is an immiscible blend from 40% to 60% wt.